QUALITY ANALYSIS OF E-LEARNING WEBSITE AT PT XYZ USING MODIFIED WEBQUAL METHOD AND IMPORTANCE PERFORMANCE ANALYSIS - Muhammad Haikal (STKIP PGRI Tulungagung, 2025)
The continuous development of information technology is one of its best features. The steady trend in the rapid advancement of information technology has created a necessity for institutions to adapt in order to remain competitive in this era. Considering the large number of website users in Indonesia, it is evident that the quality of websites as a medium for disseminating information is crucial. This research measures the quality of the e-learning website at PT XYZ using the Modified Webqual and Importance Performance Analysis methods. The Modified Webqual method is an extension of the Webqual 4.0 method, used to measure website quality based on four components: Usability Quality, Information Quality, Interaction Quality, and Privacy and Security. Meanwhile, Importance Performance Analysis is used to measure user satisfaction based on expectations of website quality. Data was collected through questionnaires and then subjected to validity and reliability tests, descriptive analysis, and gap analysis between user perceptions and expectations. Subsequently, the data was categorized using the Importance Performance Analysis method. The final results indicated that the e-learning website at PT XYZ has not yet met user expectations, as indicated by the gap analysis with a value 0, meaning that user importance or expectations are still higher than the website's performance. This research is part of a collection of articles and papers on the evaluation of the quality of various online platforms, including e-learning websites, and the research methods used are evaluative and quantitative in nature